Simulacra of Humanity in Klara and the Sun by Kazuo Ishiguro (2021) - Chairani, Raja Ayudia Putri; Alamsyah, Devy Kurnia (English Language and Literature, 2024)
This study examines Kazuo Ishiguro's novel Klara and the Sun (2021) through the lens of postmodernism, particularly focusing on Jean Baudrillard's concept of Simulacra and Simulation. Using a descriptive qualitative approach, the research investigates how the novel depicts the creation of false consciousness through simulacra and the subsequent impact on arising consequences to humanity. There are two key findings emerge from the analysis. First, the simulacra in the novel that contribute to the creation of false consciousness among the characters, thereby blurring the distinction between reality and simulation. Second, the resulting consequences of the false consciousness on humanity include dehumanization, social segregation, and increased reliance on technology. These findings underscore the ethical and existential challenges posed by the advancement of technology.